(untitled) (Journal of Association of Clinical Endocrinologist and Diabetologist of Bangladesh, 2025)
Background: Hyperglycemia is a frequent finding in acute intracerebral hemorrhage (ICH), but there is debate concerning its prognostic significance. Objective: To investigate the impact of blood glucose (BG) measured during admission on short-term mortality and functional outcome in hospital-admitted patients with acute ICH. Methods: This prospective cohort study included 224 ICH patients [age 60 (50-70) years, median (IQR); female 99 (44.2%)] in the stroke unit of the National Institute of Neurosciences and Hospital Dhaka, Bangladesh from July 2019 to December 2019. All patients underwent routine clinical examination, neuroimaging, and biochemical tests. Stroke severity was assessed by the National Institutes of Health Stroke Scale (NIHSS) and Glasgow Coma Scale (GCS). Capillary BG was measured using a standardized glucometer. BG level ≥10 mmol/L was used as the cut-off for elevated BG. Mortality was noted and functional assessment was done by modified Rankin Scale (mRS) score at 30 days from ictus. Result: The NIHSS score, ICH volume, and frequency of aspiration pneumonia were significantly higher whereas the GCS score was significantly lower in the elevated BG group (p=0.002, 0.036, 0.022, and 0.022 respectively). In-hospital mortality, mortality after 30 days, and mRS score after 30 days were also higher in the elevated BG group (p=0.003 in all). Cumulative survival of ICH patients was significantly lower in the elevated BG group after 30-days of acute stroke event (p<0.001). When adjusted for age, creatinine, presence of aspiration, midline shift in CT scan, volume, site, and ventricular extension of ICH, multivariate Cox regression revealed that admission BG could independently predict the mortality 30 days after ICH [HR 1.11 (95%CI 1.06-1.16; p<0.001). Conclusions: In patients with acute ICH, admission BG is linked to an increase in 30-day and in-hospital mortality rates. J Assoc Clin Endocrinol Diabetol Bangladesh, January 2022; 1 (1): 15-21